Implementation of Islamic Business Ethics: The Case of MSMEs in Sukoharjo, Indonesia - Ma'ruf, Aminudin; Mukhlisin, Fajar Sidiq; Rohmaningtyas, Nurwinsyah (Niqosiya: Journal of Economics and Business Research, 2024)
Introduction: Islam urges every Muslim to work and comply with all Islamic principles. The Centre of Statistical Data (BPS) of Sukohajo noted that 94.8% of Sukoharjo’s population is Muslim. This indicates that Sukoharjo has great economic potential, especially in the field of halal lifestyle. This paper conducted a study with the aim to analyse the application of Islamic business ethics to Micro, Small, and Medium Enterprises (MSMEs) in Sukoharjo. Research Methods: This research employs a qualitative analysis with a descriptive analysis method. Primary data were obtained through interviews and documentation with 28 MSMEs in Sukoharjo as the research sample. The data is then analysed by data reduction, data display, and data verification. Results: The result shows that the majority of MSMEs in Sukoharjo Regency have implemented Islamic business ethics such as honesty, fairness, greetings, trust, and selling halal products. However, religious activities for employees lack the practices. There are several internal and external factors shaping the implementation of Islamic business ethics of MSMEs in Sukoharjo, namely internal factors (beliefs) and external factors (science, family, social environment, experience, and type of business). Conclusion: The study humbly urges the Indonesian Ulema Council to incorporate Islamic business ethics in their teachings, shaping a better understanding of society and leading the optimisation of the application.